Fragile X Syndrome Workshop - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The proceedings of the 9th International Workshop on Fragile X Syndrome and X-Linked Mental Retardation, held in Strasbourg, France, are reported from the University Hospital of Leuven, Belgium.